Fundamentals of Managerial Economics - Hirschey, Mark and Pappas, James L. (Chicago The Dryden Press, 1998)
This text aims to equip students with a solid foundation in economic understanding to use in managerial decision making. A variety of examples and simple numerical problems illustrate the application of managerial economics to an assortment of practical situations.
Include Index, Appendix and References
Keywords: Managerial economics